Diterpenes from the stem bark of Euphorbia neriifolia and their in vitro anti-HIV activity. (January 2018) - Yan, Shi-Li; Li, Yan-Hong; Chen, Xuan-Qin; Liu, Dan; Chen, Chin-Ho; Li, Rong-Tao
Abstract: Six previously undescribed diterpenoids, named euphorantins S–T and euphorneroids A–D, including ingol and ent -atisane types, along with eleven known diterpenoids, were isolated from Euphorbia neriifolia . Their structures were elucidated on the basis of extensive NMR analysis and high resolution mass spectrometry. Euphorneroid D and ent -3-oxoatisan-16 α, 17-acetonide exhibited moderate anti-HIV-1 activities, with EC50 values of 34 μ M (SI = 2.3) and 24 μ M (SI = 1.9), respectively. Graphical abstract: The EtOAc extract of Euphorbia neriifolia exhibited potent anti-HIV activity. Six previously undescribed diterpenoids were isolated from the extract. Two ent -atisane diterpenoids showed moderately active in anti-HIV1. Image 1 Highlights: The EtOAc extract of E. neriifolia exhibited anti-HIV-1 activity from the bioassay screening of 23 plant species extract. Six previously undescribed diterpenoids were isolated from the extract. Two diterpenoids exhibited moderate anti-HIV-1 activity.